BIODIVERSITY OF THE ALTAI REGION IN THE CONTEXT OF SUSTAINABLE TOURISM DEVELOPMENT: EXPERIENCE OF TRANSBOUNDARY COOPERATION - Zhumakan Samgar, Han Fang, Aiganym Baizakova, Aday Sekenuly, Ordenbek Mazbayev (Вестник ЗКУ, 2025)
The article analyzes the current state of biodiversity in the Altai region, as well as the role of tourism and key research directions in its conservation. Particular attention is paid to the impacts of ecotourism, nature-based tourism, and other forms of tourism on natural ecosystems. The study emphasizes effective practices of transboundary cooperation among Kazakhstan, Russia, China, and Mongolia, highlighting the importance of initiatives aimed at protecting international tourist destinations and implementing joint programs. The authors substantiate that the introduction of sustainable tourism principles makes it possible not only to conserve natural resources but also to ensure the socio-economic development of local communities. In addition, the application of integrated management approaches, the implementation of scientific monitoring, and the strengthening of international partnerships are identified as key conditions for the long-term conservation of biodiversity in the Altai region. The research findings have practical significance for the management of transboundary natural areas and the development of sustainable tourism strategies.